Anesthesia for Pygopagus Conjoined Twins During Single-Twin and Simultaneous Pneumoperitoneum: A Case Report. Issue 3 (1st August 2018) - Sara, John-Paul; Kydes, Ashley; Pryjdun, Olena; Jacoby, Michael; McBride, Whitney; Pandya, Samir; Barst, Samuel
Abstract : We present the case of the first stage of separation of 9-month-old pygopagus conjoined twins who demonstrated minimal shared vasculature on preoperative imaging and no cross-sedation or cross-neuromuscular blockade during separate inductions of anesthesia. Laparoscopy was implemented in 1 twin at a time, then in both twins simultaneously. Despite insufflation of a single-twin's abdomen, both twins demonstrated hypercapnia and signs of a concomitant respiratory acidosis because of carbon dioxide diffusion through a shared peritoneal membrane. This is the first documented case of simultaneous laparoscopy-induced pneumoperitoneum in pygopagus conjoined twins.